Analysis of Performance Decline in 415.15 kWp On-Grid Solar Based on Dust Soiling Factors and Inverter Temperature in the Solar Power System - Muhammad Athallah Al Daffa; Bintang Cahyo Nugroho; Nur Alif Mardiyah; Khusnul Hidayat (Interdisciplinary Social Studies, 2025)
This study aims to analyze the influence of soiling factors and inverter temperature on the performance degradation of solar panels, using real-time data captured through sensors. Soiling, which includes the accumulation of dust and dirt on the surface of solar panels, as well as fluctuating inverter temperatures, are known to affect energy conversion efficiency. Tests were conducted by monitoring the performance of solar panels under different soiling conditions and varying inverter temperatures. To solve the soiling problem, cleaning was carried out on the solar panels, while the high inverter temperature was handled by adding a fan to the room to increase air circulation and cool down the inverter temperature. The results show that soiling can reduce energy conversion efficiency, while high inverter temperatures worsen system performance. Periodic cleaning of the solar panels was found to be effective in improving efficiency, while the addition of a fan in the room can reduce energy losses caused by high inverter temperatures. These findings provide important insights for performance optimization of solar panels and inverter systems under field conditions.